Peran Self Esteem Dalam Mencegah Bullying Di SD: A System Literatur Review - Rima Melati; Nur Azmi Alwi (Lembaga Pengembangan Kinerja Dosen, 2024)
Elementary school learning is often an important context in understanding the role of self-esteem in preventing bullying. In situations where direct interaction is limited, the role of self-esteem is key in shaping students' responses to social pressures such as bullying. This study aims to conduct a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method to explore how self-esteem influences and can be used to prevent bullying at the elementary school level. This article presents an in-depth literature review related to the role of self-esteem in preventing bullying in elementary school environments. By analyzing eight related articles, this study identified that high self-esteem acts as a significant protective factor against the tendency to become victims of bullying. On the other hand, children with low self-esteem tend to be more vulnerable to bullying behavior. The findings of this study highlight that self-esteem plays an important role in reducing bullying behavior among elementary school students. The selected articles suggest that increasing self-esteem can reduce the likelihood of bullying and help students cope with potentially detrimental social pressures.